Safety and efficacy of liraglutide in patients with type 2 diabetes and end-stage renal disease: protocol for an investigator-initiated prospective, randomised, placebo-controlled, double-blinded, parallel intervention study. Issue 4 (26th April 2013) - Idorn, Thomas; Knop, Filip K; Jørgensen, Morten; Jensen, Tonny; Resuli, Marsela; Hansen, Pernille M; Christensen, Karl B; Holst, Jens J; Hornum, Mads; Feldt-Rasmussen, Bo
Abstract : Introduction: Diabetes is the leading cause of end-stage renal disease (ESRD). Owing to renal clearance, several antidiabetic agents cannot be used in patients with ESRD. The present protocol describes an investigator-initiated trial aiming to test safety and efficacy of treatment with the glucagon-like peptide-1 receptor agonist liraglutide in patients with type 2 diabetes and dialysis-dependent ESRD. Methods and analysis: Twenty patients with type 2 diabetes and ESRD will be compared with 20 matched patients with type 2 diabetes and normal kidney function in a randomised, parallel, placebo-controlled (1 : 1), double-blinded setting. All participants will receive 12 weeks of daily treatment with liraglutide/placebo in an individually titrated dose of 0.6, 1.2 or 1.8 mg. Over nine visits, plasma liraglutide, glycaemic control, β-cell response, cardiovascular parameters, various biomarkers and adverse events will be assessed. The primary endpoint will be evaluated from dose-corrected plasma trough liraglutide concentration at the final trial visit to determine potential accumulation in the ESRD group. Ethics and dissemination: The study has been approved by the Danish Medicines Agency, the Scientific-Ethical Committee of the Capital Region of Denmark and the Danish Data Protection Agency. An external monitoring committee (The Good Clinical Practice Unit at Copenhagen University Hospitals) will oversee the study. The results of the study will be presented at national and international scientific meetings, and publications will be submitted to peer-reviewed journals. Trial registration: ClinicalTrials.gov Identifier: NCT01394341